A Path Smoothing Strategy Based on Harmony Search Algorithm for Probabilistic Foam - Nascimento, Luı́s B. P.; Santos, Vitor G.; Pereira, Diego S.; Alsina, Pablo J. (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS), 2019)
Probabilistic Foam method (PFM) is an attractive path planner, ideal for applications in assistive robotics which demands safety. However, its planned paths are not smooth. Then, path smoothing strategies need to be applied for PFM to improve the paths. This paper presents an optimization approach based on Harmony Search algorithm to smooth PFM paths. Simulated experiments using an exoskeleton to overcome an obstacle were performed to test our methodology. Results show that our approach is capable of smoothing paths for the exoskeleton, which results in more anthropomorphic motions.